CRIMINAL-LEGAL REGULATION OF DEEPFAKES: THE EXPERIENCE OF UZBEKISTAN - Fazilov, Farkhod (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2025)
The article examines the criminal-legal regulation of deepfakes in Uzbekistan in a comparative perspective with foreign jurisdictions. Deepfakes — synthetic media generated by artificial intelligence — pose growing threats to privacy, reputation, democracy, and cybersecurity. The author analyzes doctrinal debates among scholars about whether to create new criminal offenses or expand existing ones, emphasizing proportionality and the balance between technological progress and protection of human rights. The study concludes that effective criminal-law policy must combine legal, technical, and educational measures, including clear definitions of harmful deepfakes, improved forensic expertise, and international cooperation in combating AI-based manipulation.